The Myth of the ‘Ideal Offender’: Challenging persistent human trafficking stereotypes through emerging Australian cases - Raby, Kyla; Chazal, Nerida (Anti-Trafficking Review, 2022)
Human trafficking and slavery offences are often constructed through prominent stereotypes of the ideal victim and the ideal offender. This article examines four common offender stereotypes created by representations of trafficking seen in the media, popular culture, government reports, and awareness campaigns, and challenges these stereotypes by comparing them with international and Australian research and statistics. This comparison demonstrates that the ideal trafficking offender is a myth that must be broken. To support this argument, the article explores two emerging Australian cases involving sexual exploitation and allegations of slavery and servitude that significantly depart from stereotypical representations of trafficking. This shows the limitations of offender stereotypes in explaining trafficking offences and demonstrates the need for greater emphasis on the role of coercive control in trafficking offences, the impact of trust and changing relationships, and the interrelationship of trafficking with domestic violence.